Alternatif fonlama kaynağı olarak sendikasyon kredileri ve Türk bankacılık sistemine yönelik bir uygulama - Çetintaş, Umut (My University, 2008)
Türk Bankacılık sektörü için oldukça uzun bir süredir önemli bir fon kaynağı oluşturan sendikasyon kredileri son dönemde tüm firmalar için önemli bir kaynak olma özelliğini kazanmıştır. Sendikasyon kredilerinin Türk bankaları için alternatif bir fonlama enstürmanı olup olmadığının etraflıca tartışıldığı tezde, ayrıca kredi veren bankaların aynı özellikteki borçlular arasındaki tercihlerinin sebeplerine ve daha az getiri sunan birincil piyasa katılımının ikincil piyasada daha iyi şartlarla sendikasyon kredisi alınmasına tercih edilmesinin arkasındaki sebeplere de yer verilmektedir. Yapılan detaylı araştırmada ulaşılan sonuç Türk bankalarının aldığı sendikasyon kredilerinin, hem borçlu hem de kredi veren tarafından “ilişki bazlı finansal enstrüman” olarak görüldüğü yönündedir.

Syndicated credits have been very important source of funding for Turkish Banks for a long period of time and for other non-bank firms recently. In this thesis we are trying to find out if syndicated credits are really alternative funding source for Turkish Banks. We are also trying to understand what is the reason of creditor banks’ participating in one borrower bank’s syndicated loans while being absent in other banks’ facilities and why creditor banks participate in Turkish banks’ syndicated loans while there are better conditions for the similar loans in the secondary market. We claim that main answer for these questions are related with what kind of financial instrument syndicated loans are and how they are perceived by both creditors and borrowers as far as Turkish banking market is concerned. As a result of our research, we come up with the result that syndicated loans are mainly considered to be part of relationship between the parties. Since it is not perceived as a member of transaction-driven financial instrument family in the Turkish market where Turkish bank are borrowers , we suggest how Turkish banks as well as non-bank firms can make use of this alternative source of funding in a more efficient and better way.
Keywords: Bankalar ve Bankacılık; Fon; Kredilendirme_Bankalar ve Bankacılık; Krediler